Experimental Study of Diamond Burr Polishing Methods of Bowman’s Membrane - S. V. Trufanov; A. A. Fedorov; V. R. Mamikonyan; L. Yu. Tekeeva; S. A. Malozhen; A. A. Karamyan (Oftalʹmologiâ)
Purpose: to develop the optimal (safe and effective) method of diamond burr polishing of Bowman’s membrane (DBPBM) for the possible use it in the treatment of the recurrent corneal erosion syndrome (RCES) in the experiment.Material and methods. DBPBM in different modifications of the  method and the mechanical deepithelization were performed in  experiment on 19 human cadaver eyes. We use system Ophtho-Burr  for DBPBM that includes a tip and ophthalmic burrs with diameter  1mm, 2.5 mm, 5 mm, varying the speed of rotation of burr. For 3  eyes — polishing with the application of burr with a diameter of 5  mm, the rotation frequency of 4000 rpm using 2 passes over the  surface of the cornea. For 3 eyes — burr with a diameter of 2.5 mm,  rotation frequency of 4000 rpm in 2 perpendicular passes. For 3 eyes — diameter burr 1 mm at speed of 8000 rpm in 2 perpendicular  passes. For 3 eyes — diameter burr 1 mm at speed 4000 rpm with 4  passes along the surface of the cornea. For 4 eyes — diameter was 1 mm at speed of 4000 rpm in 2 perpendicular passes. For 3 the eyes  was conducted mechanical deepithelization. Subsequent histopathological investigation of the cornea was  performed by method of semi-thin section, with polychrome staining.Results. The obtained results of histological studies of DBPBM in  different versions on cadaver cornea is allowed to choose the optimal variant of surgical intervention for use in clinical conditions. It  consisted in a selection of burr with a diameter of 1 mm, the rotation frequency of the 4000 rpm and 2 perpendicular passes with a  moderate compression of the cornea. The abovementioned technique of intervention allows removing completely the corneal epithelium  with a basal membrane and save uniform in thickness, fully  deepitelizationed Bowman’s membrane.Conclusion. Careful and accurate removal of dysplastic corneal epithelium in cases of the recurrent corneal erosion syndrome using  proposed method in clinical conditions should contribute to the  creation optimal environments for adequate reepithelization with  steady epithelial-stromal adhesion. The remaining nearly intact  Bowman’s membrane after procedure can prevent some postoperative complications such as haze and induced refractive disorders.